Analysis of the completion of the safe surgery checklist in a public hospital in the Federal District - Barbosa Ferreira, Juscilene (2022)
Introduction:The World Health Organization instituted the Surgical Safety Checklist, a tool consisting of safety items that must be checked at three times during surgery. Objective: To analyze the completeness of filling out the LVSC in a public hospital in the Federal District.Methodology: Cross-sectional, retrospective, descriptive study with a quantitative approach. The sample had 607 checklists used by the institution of the study, consisting of four phases.Results: All steps were completed in 306 procedures (50.4%). The entry was fully filled in 600 surgeries (98.8%), the sign in had its items checked completely in 408 procedures (67.2%), the time out showed completeness in 407 surgeries (67.5%) and the sign out was complete in 543 operative procedures (89.4%). As for adherence to the items in each stage, at entry the elements had 99.4% adherence, at sign in, adherence was 96.1%, at time out it was 92.7% and at sign out, 96. 1%.Conclusion: Despite good adherence to all safety items, instrument adherence was unsatisfactory. Constant evaluation of the procedure is suggested to promote an institutional culture focused on patient safety.